Delayed patient isolation and associated factors during the mpox outbreak in Uganda, July-December 2024 - (:unkn) unknown (Elsevier, 2025)
Objective: Rapid detection and isolation of mpox mpox patients reduces transmission. We assessed delays in patient isolation and associated factors during the mpox outbreak in Uganda from July to December 2024 to inform response efforts. Methods: We selected all laboratory-confirmed cases isolated at two mpox isolation centers in Uganda from July 24 to December 29, 2024. Time-to-Isolation (TTI) was number of days from symptom onset to isolation, categorized as ‘short’ (0-3 days) or ‘delayed’ (>3 days) based on operational benchmarks for rapid containment of a highly infectious disease and the biological urgency of early isolation of mpox cases. We summarized data from case narratives into descriptive statistics and used multivariable logistic regression to measure the level of association of individual factors with delayed TTI which was the outcome variable. Reasons for short or delayed TTI were obtained from qualitative interviews. Results: Among 832 mpox patients, 709 (91%) had delayed TTI, 473 (57%) were males, 713 (86%) were ≥18 years old, 698 (83%) had not visited a health facility before isolation, and 742 (89%) had self-medicated before isolation. Age ≥18 years (aOR = 2.6, 95% CI = 1.6-4.2) and self-medication (aOR = 5.4, 95% CI = 1.7-17.1) were associated with delayed TTI. Interviewed mpox patients with delayed TTI (n = 9) attributed this to lack of diagnostic skills among healthcare workers and attributed their delayed care-seeking to personal economic concerns. Mpox patients with short TTIs (n = 6) attributed this to prior knowledge about mpox from social media and response teams. Conclusion: Most mpox patients experienced delayed TTI, associated with being older than 18 years and self-medication, and driven by misdiagnosis and individual economic concerns. Targeting risk communication and strengthening frontline diagnostic capacity could improve early case detection and management.